PEMASARAN POLITIK DAN KELOMPOK KEPENTINGAN: MEMPERJUANGKAN ISU-ISU GENDER DALAM PEMILU - ATHIK HIDAYATUL UMMAH (TASÂMUH, 2019)
Political marketing is the application of marketing principles and procedures in political campaigns by various individuals and organizations. To win the election, candidates need to understand the market, they are voters and their basic needs and aspirations that want candidates to represent. To fight and goal their aspirations, they establish groups as their streght. Interest groups handle an important role in democracy, even interest groups are more influential in making decisions than formal decision-making institutions. Learning from presidential elections in America and Britain provides important lessons for the field of political communication. The presidential candidate who won the presidency cause targeting women’s voters and fighting for gender issues. That is because the number of woman voters is quite large and they tend to be more loyal to their choices. The elected president uses good strategy and public opinion according to interest groups and gender differences. In Indonesia, the president-vice president candidate also targeting women's voters with various narratives, strategies and action programs